(3GdJPcQI GdgOhjI aj GdMjd GdMQHjIs - (3Ydj Hf CHj HcQ Hf Ydj GdgQhj, CHh GdMSf,J (B611 (3g` s
(3ChdgG (B:s
(3hHYO haGJg deG SCdJi GdCN GdUGdM , hGdNd GdfGUM , Cf CUfa dg cJGH (B" (3hCHhHg CHhGHkG (B" s
(3BNQgG (B:s
(3hjQJaY Hg GdCQjH hjSJYjf HgG GdSdWGf Ydi ef fGhCI hGdedc Ydi ef YGOGI hGdMeO ddg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B266 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B47s
(3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B879 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQaI YGeI (B- (3U (B12 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI YGWa CafOi (B/ (3GSJGfHhd (B(2018) s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs